STUDY OF ITEMS ABOUT DAILY ASSESSMENT MADE BY TEACHERS OF PLANT TISSUE STRUCTURE AND FUNCTION MATERIAL GRADE XI SMA SCHOOL YEAR 2020/2021 - Asri, Faradillah; Raharjo, Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Abstract This research is motivated by the low percentage of daily assessment of plant tissue structure and function material of 37.8%. The daily assessment problem that has been tested to students has never been analysis, therefore researchers aim to describe the quality of the problem, improve the problem and obtain better quality questions in the daily assessment made by teachers of plant tissue structure and function materials at SMAN 20 Surabaya school year 2020/2021. This research is descriptive research with qualitative and quantitative methods. Data collection techniques are carried out through interview techniques, studies, and tests using the instrument sheet daily assessment made by teachers 25 multiple choice questions and 4 essays, problem improvement sheets, latticework made by teachers, and student answer sheets. The subjects of this study were 30 students from grade XI IPA 3 SMAN 20 Surabaya.The results showed the reliability value of the teacher's problem was 0.64, the difficulty level showed 2 difficult questions (8%), 9 medium questions (35%), 7 easy questions (28%) and 7 very easy questions (28%). the differentiating index shows 8 very good questions (32%), 6 good questions (24%), 4 questions are enough (16%) ; distractors show 3 very good questions (12%), 2 good questions (8%), 6 questions are enough (24%), 5 questions are bad (20%), and 9 questions are very bad (36%). Daily assessment questions of function material and plant tissue structure made by teachers can be concluded to have low reliability, low difficulty level, good difference index, and bad distractor. Improvement item can be concluded to have high reliability, medium difficulty level, highly good difference index, highly good distractor. Keywords: Study of item question , Daily assessment, Plant tissue structure and function Abstrak Penelitian ini dilatarbelakangi oleh rendahnya persentase penilaian harian struktur jaringan tanaman dan fungsi bahan sebesar 37,8%. Soal asesmen sehari-hari yang diujikan kepada siswa belum pernah dianalisis, oleh karena itu peneliti bertujuan untuk mendeskripsikan kualitas soal, memperbaiki masalah dan mendapatkan soal yang lebih berkualitas dalam asesmen harian yang dilakukan oleh guru materi struktur dan fungsi jaringan tumbuhan di SMAN. 20 Surabaya tahun pelajaran 2020/2021. Penelitian ini merupakan penelitian deskriptif dengan metode kualitatif dan kuantitatif. Teknik pengumpulan data dilakukan melalui teknik wawancara, pembelajaran, dan tes dengan menggunakan instrumen lembar penilaian harian yang dibuat guru sebanyak 25 soal pilihan ganda dan 4 karangan, lembar perbaikan masalah, kisi-kisi yang dibuat oleh guru, dan lembar jawaban siswa. Subjek penelitian ini berjumlah 30 siswa kelas XI IPA 3 SMAN 20 Surabaya, Hasil penelitian menunjukkan nilai reliabilitas soal guru sebesar 0,64, tingkat kesulitan menunjukkan 2 soal sulit (8%), 9 soal sedang (35%), 7 pertanyaan mudah (28%) dan 7 pertanyaan sangat mudah (28%). indeks pembeda menunjukkan 8 pertanyaan sangat baik (32%), 6 pertanyaan baik (24%), 4 pertanyaan cukup (16%); distraktor menunjukkan 3 pertanyaan sangat baik (12%), 2 pertanyaan baik (8%), 6 pertanyaan cukup (24%), 5 pertanyaan buruk (20%), dan 9 pertanyaan sangat buruk (36%). Soal penilaian harian materi fungsi dan struktur jaringan tanaman yang dibuat oleh guru dapat disimpulkan memiliki reliabilitas rendah, tingkat kesulitan rendah, indeks selisih baik, dan distraktor buruk. Item perbaikan dapat disimpulkan memiliki reliabilitas tinggi, tingkat kesulitan sedang, indeks selisih sangat baik, distraktor sangat baik. Kata Kunci: Telaah, Penilaian Harian, Struktur dan fungsi jaringan tumbuhan